Analisis Kualitas Produk Air Filter Menggunakan Basic Seven Tools di PT. Batarasura Mulia - Shyntia Cahyani; Sukanta Sukanta (Jurnal Ilmiah Wahana Pendidikan, 2022)
Quality control is an activity that must be carried out by the company so that the products produced are according to the standards set by the company in meeting customer satisfaction. This research was conducted to obtain the results of the analysis of water filter products at PT. Honorable Batarasura. This research is solving problems using the seven tools method. This seven-tool method uses 7 quality control tools, namely Check Sheet, Control Chart, Cause and Effect Diagram, Pareto Diagram, Histogram, Scatter Diagram and Stratification so as to produce measurements that show the extent to which management goals are achieved. From the analysis using seven problem point finding tools that have been analyzed lie in several aspects, including aspects of methods, materials, machines, humans and the environment. From several aspects of influence, the most dominant aspect lies in the human aspect.